Rapid determination of volatile constituents in safflower from Xinjiang and Henan by ultrasonic-assisted solvent extraction and GCâMS - Ling-Han Jia; Yi Liu; Yu-Zhen Li (Elsevier, 2011)
The total volatile components were extracted from safflower by ultrasonic-assisted solvent extraction (USE) and their chemical constituents were analyzed by gas chromatographyâmass spectrometry (GCâMS) to provide scientific basis for the quality control of safflower. Five different solvents (diethyl ether, ethanol, ethyl acetate, dichloromethane and acetone) were used and compared in terms of number of volatile components extracted and the peak areas of these components in TIC. The results showed that USE could be used as an efficient and rapid method for extracting the volatile components from safflower. It also could be found that the number of components in the TIC of ethyl acetate extract was more than that in the TIC of other solvent ones. Meanwhile, the volatile components of safflower from Xinjiang Autonomous Region and Henan Province of China were different in chemical components and relative contents. It could be concluded that both the extraction solvents and geographical origin of safflower are responsible for these differences. The experimental results also indicated that USE/GCâMS is a simple, rapid and effective method to analyze the volatile oil components of safflower. Keywords: Safflower, Ultrasonic solvent extraction, Gas chromatographyâmass spectrometry (GCâMS)